Strength training intervention for adult individuals with knee osteoarthritis: Establishing fidelity - Küçük, Hamza; Ghadamyari, Niloufar; Şahin, Fatma Neşe; Çiçek, Güner; Ceylan, Tülay; Güler, Özkan; Yaşar, Onur Mutlu; Şensoy, Cüneyt; Arslanoğlu, Cansel; Doğan, Erol; Arslanoğlu, Erkal (Frontiers in Physiology, 2025)
BackgroundKnee osteoarthritis (KOA) is a prevalent chronic condition among the adult individuals, leading to pain, joint stiffness, and muscle weakness. Resistance training is an effective strategy for alleviating KOA-related symptoms and improving physical function. However, the efficacy of such interventions also depends on their fidelity, ensuring that the prescribed exercise protocols are followed correctly. This study aimed to assess the fidelity of a structured strength training program and its effects on pain management in adult individuals with KOA.MethodsA total of 72 adults (mean age = 56.27 ± 4.89 years), approximately 40% of whom were overweight, were randomly assigned to either a strength training group (n = 37) or a control group (n = 35). Quantitative data were collected using the Knee Injury and Osteoarthritis Outcome Score (KOOS), while qualitative data on intervention fidelity were obtained through self-reported adherence to daily home workouts.ResultsThe results indicated a significant improvement in KOOS scores in the strength training group compared to the control group (p < 0.001). Participants consistently adhere to the prescribed exercise program in their home workouts. These findings highlight the importance of intervention fidelity in strength training programs for adult individuals with KOA, emphasizing its role in optimizing health outcomes.ConclusionThis study contributes to the growing evidence supporting structured strength training as a viable strategy for managing KOA-related symptoms and enhancing physical function in ageing populations.